Studi Kelayakan Lokasi Budidaya serta Pembuatan Masterplan di Kampung Perikanan Desa Patra Tani, Muara Enim, Sumatera Selatan - Wildan Nurussalam; Eddy Supriyono; I’ana Rahma Salisa (Jurnal Akuakultur Sungai dan Danau, 2023)
Kampung Perikanan Desa Patra Tani is located in Muara Enim Regency, precisely in Muara Belida district, a location that was once a place for aquaculture but the lack of care and management in that location has now become neglected. The objective of this research is to analyze the feasibility of land and make a master plan in Kampung Perikanan Desa Patra Tani, Muara Enim, South Sumatra as a location for aquaculture. Field observation activities include indirect (in situ) and direct (ex situ) water quality measurements at five observation stations, soil sampling, mapping using GPS, and market availability surveys. The results of data analysis on water quality using the scoring method show that in Kampung Perikanan Desa Patra Tani tends to be in the S2 class (moderately suitable) meaning that it has a few limiting factors in the waters so that several treatments are needed before cultivating. One of the commodities that are suitable for cultivation is tilapia because of high market demand is suitable to fill the shortage.